2007
DOI: 10.1016/j.ejvs.2006.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Study Comparing Routine Hospital Administrative Data with the Vascular Society of Great Britain and Ireland's National Vascular Database

Abstract: There are significant differences in total numbers between HES and the NVD. If the National Vascular Database is to become a credible source of information on activity and outcomes for vascular surgery, there is a clear need to increase the number of contributing surgeons and to increase the completeness of data submitted. Further analysis at individual record level is needed to identify other reasons for discrepancies which could help to enhance data quality, both within Hospital Episode Statistics and within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 9 publications
1
49
0
1
Order By: Relevance
“…This argument has been forwarded for clinical registers [17], Medicare data in the United States [18], and insurance data in Germany. In an exploratory study comparing claims data of German PCPs with their charts in 2003, Erler et al [19] found an underreporting in the claims data in 30% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…This argument has been forwarded for clinical registers [17], Medicare data in the United States [18], and insurance data in Germany. In an exploratory study comparing claims data of German PCPs with their charts in 2003, Erler et al [19] found an underreporting in the claims data in 30% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, error was found in both data sets, as some hospitals misclassified patients in the VAED, whereas others did not report all intensive care patients to the APD. Previous work has identified case ascertainment issues when comparing clinical and administrative data, demonstrating both misclassification in administrative data [31] and incomplete case ascertainment and selection bias in clinical databases [32]. Reviewing nonmatching cases is an important benefit of using a full-linked data set to assess care, as case ascertainment issues will diminish the accuracy of quality measurement.…”
Section: E15mentioning
confidence: 99%
“…Despite validation of the databases, none have been able to document all cases of interest, and a recent audit of the NVD reported that only about a half of all vascular cases have been submitted. 107 It has also been suggested that missing cases tend not to be missing at random, with the worst outcome data often excluded. 177 For these reasons, registries are not able to answer all the pertinent questions relating to treatments but, in combination with well-conducted RCTs, are likely to provide the best evidence for making public health decisions.…”
Section: Registry Datamentioning
confidence: 99%